Quelques réflexions sur la connaissance des reliefs et processus alpins chez les Romains - Delphine Acolat (Revue de Géographie Alpine)
During Antiquity times there existed little specific vocabulary pertaining to mountainous relief. Did Romans know what glaciers, crevasses, avalanches, rock falls, seasonal torrential erosion were? Could they estimate the height of the Alps? The phenomenon and dangers of alpine geomorphology were described by Greek and Latin authors of the Roman World mostly to warn the traveller of its consequences, in an attempt to ensure safe passage.